(untitled) (Revista Brasileira Multidisciplinar, 2022)
This research determined the phytochemical profile and evaluated the photoprotective, antimicrobial and antioxidant activities in extracts of Clidemia capitellata leaves, obtained with hexane, ethyl acetate and methanol. The phytochemical profile was determined through thin layer chromatography; tannins, flavonoids and total phenolics were measured; the antimicrobial activity was determined by Minimum Inhibitory Concentration and Minimum Microbicide Concentration in bacteria Staphylococcus aureus, Micrococcus luteus, Bacillus subtilis and Enterococcus faecalis; Escherichia coli, Serratia marcescens and Pseudomonas aeruginosa, Mycobacterium smegmatis, and the yeast Candida albicans. Antioxidant activity was evaluated through the methods of Reducing Power, DPPH sequestration and phosphomolybdenum. The C. capitellata leaves show flavonoids, tannins, triterpenes, steroids, anthraquinones and essential oils; tannins, flavonoids and total phenolics were extracted in greater amounts with methanol, however, the acetate extract stood out in relation to antimicrobial activity, and none of the extracts showed photoprotective activity within the values established by Brazilian legislation. Word keys: secondary metabolites. antioxidant. antimicrobial.